Phylogenomics and species delimitation for effective conservation of manta and devil rays. Issue 24 (9th November 2020) - Hosegood, Jane; Humble, Emily; Ogden, Rob; de Bruyn, Mark; Creer, Simon; Stevens, Guy M. W.; Abudaya, Mohammed; Bassos‐Hull, Kim; Bonfil, Ramon; Fernando, Daniel; Foote, Andrew D.; Hipperson, Helen; et al.
Abstract: Practical biodiversity conservation relies on delineation of biologically meaningful units. Manta and devil rays (Mobulidae) are threatened worldwide, yet morphological similarities and a succession of recent taxonomic changes impede the development of an effective conservation strategy. Here, we generate genome‐wide single nucleotide polymorphism (SNP) data from a geographically and taxonomically representative set of manta and devil ray samples to reconstruct phylogenetic relationships and evaluate species boundaries under the general lineage concept. We show that nominal species units supported by alternative data sources constitute independently evolving lineages, and find robust evidence for a putative new species of manta ray in the Gulf of Mexico. Additionally, we uncover substantial incomplete lineage sorting indicating that rapid speciation together with standing variation in ancestral populations has driven phylogenetic uncertainty within Mobulidae. Finally, we detect cryptic diversity in geographically distinct populations, demonstrating that management below the species level may be warranted in certain species. Overall, our study provides a framework for molecular genetic species delimitation that is relevant to wide‐ranging taxa of conservation concern, and highlights the potential for genomic data to support effective management, conservation and law enforcement strategies.